HRM, Employee Share Ownership and Corporate Performance. - Michie, J; Oughton, C (2003)
A great deal of interest has been generated on understanding linkages between work commitment, job motivation and productivity. The purpose of this paper is to consider the link between employee commitment and motivation, on the one hand, and productivity on the other, and in particular whether employee share ownership can play a positive role in this regard. The focus is, therefore, on the effects of employee share ownership and employee participation on corporate performance. A departure point is the UK government’s policies to promote employee share ownership, which has been presented explicitly as a means to boost productivity via enhanced employee commitment and motivation. How employee share ownership may enhance corporate performance in terms of impacting on corporate governance is also discussed.